2002
DOI: 10.1002/humu.10092
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutation profile ofMEN1in multiple endocrine neoplasia type 1: search for correlation between phenotype and the functional domains of the MEN1 protein

Abstract: Multiple Endocrine Neoplasia type 1 (MEN1) is an autosomal dominant disease characterized by endocrine tumors of the parathyroids, the pancreatic islets, and the anterior pituitary. The MEN1 gene encodes menin, a nuclear protein interacting with JunD/AP1, Smad3, NFkappaB, and other proteins involved in transcription and cell growth regulation. Here, by exhaustive sequence analysis of 170 probands/families collected through a French clinical network, we identified 165 mutations located in coding parts of the ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
99
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 55 publications
5
99
1
2
Order By: Relevance
“…These data are supported by murine models of men1 gene knockout, in which w37% of heterozygotic animals had pituitary tumors in adulthood (8). While no genotype-phenotype relation has been shown among the hundreds of MEN1 mutations now described, in familial MEN1, pituitary disease is significantly more frequent than in sporadic MEN1 cases (9). Prolactinomas predominate in MEN1, are larger than their sporadic counterparts and have a poorer response to dopamine agonist therapy (7).…”
Section: Men1mentioning
confidence: 96%
“…These data are supported by murine models of men1 gene knockout, in which w37% of heterozygotic animals had pituitary tumors in adulthood (8). While no genotype-phenotype relation has been shown among the hundreds of MEN1 mutations now described, in familial MEN1, pituitary disease is significantly more frequent than in sporadic MEN1 cases (9). Prolactinomas predominate in MEN1, are larger than their sporadic counterparts and have a poorer response to dopamine agonist therapy (7).…”
Section: Men1mentioning
confidence: 96%
“…Mutation analysis of the MEN1 gene allows the early identification of asymptomatic carriers, years before any MEN1-associated biochemical and/or instrumental abnormalities are detected [6,8]. Unfortunately, as reported by the great majority of worldwide epidemiology studies, a genotype-phenotype correlation, like in MEN2 syndromes, has not clearly been identified in MEN1 syndrome, strongly reducing the possibility to foresee exact future clinical manifestations of the disease by the specific gene mutation [6,[9][10][11][12]. Recently, two studies by the "Groupe d'étude des tumors endocrines (GTE)" reported a trend for intrafamilial correlation in disease expression and severity and in heritability of MEN1 tumors [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, no clinically relevant genotype-phenotype correlation has been established to date. (7,13) A diagnostic DNA test for MEN1 germline mutations is beneficial to the patients with endocrine tumors suggestive of MEN1 and offspring of MEN1 patients.(2) However, it is often difficult to distinguish a disease-causing mutation from a rare benign polymorphism especially when it is a novel missense mutation found in a patient with incomplete forms of MEN1. We previously demonstrated that menin missense mutants associated with typical MEN1, defined as the occurrence of tumors in at least two of the three main MEN1-related endocrine tissues, are degraded rapidly by the ubiquitin-proteasome pathway when expressed in culture cells.…”
mentioning
confidence: 99%
“…However, no clinically relevant genotype-phenotype correlation has been established to date. (7,13) A diagnostic DNA test for MEN1 germline mutations is beneficial to the patients with endocrine tumors suggestive of MEN1 and offspring of MEN1 patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation